Sociolinguistic interaction and identity construction: The view from game-theoretic pragmatics - Heather Burnett (Journal of Sociolinguistics, 2017)
Understanding the dynamics that characterize interaction between conversational participants is a fundamental goal of most theories of socially conditioned language use and identity construction through language. In this paper, I outline a class of formal tools that, I suggest, can be helpful in making progress towards this goal. More precisely, this paper explores how Bayesian signalling game models can be used to formalize key aspects of current sociolinguistic theories, and, in doing so, contribute to our knowledge of how speakers use their linguistic resources to communicate information and carve out their place in the social world. The Bayesian framework has become increasingly popular for the analysis of pragmatic phenomena of many different types, and, more generally, these models have become a dominant paradigm for the explanation of non-linguistic cognitive processes. As such, I argue that this approach has the potential to yield a formalized theory of personal and social identity construction and to situate the study of sociolinguistic interaction within a broader theory of rationalistic cognition.